Model Pembelajaran Think Pair Share terhadap Kemampuan Berpikir Kreatif Matematis Ditinjau dari Adversity Quotient - Soimah, Lili (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
This study is motivated by the very low students' mathematical creative thinking ability in class VIII Junior High School 13 Magelang. The purpose of this study is to analyze the effectiveness of the Think Pair Share and Student Team Achievement Division learning models on students' mathematical creative thinking ability in terms of adversity quotient. This study used quantitative research with a posttest-only control design research design. There were two classes as samples in this study, namely the experimental class of 25 students and the control class of 26 students. The sampling technique uses cluster random sampling technique. The research instruments used in this study consisted of interview guidelines, observation sheets, tests of mathematical creative thinking skills, and adversity quotient questionnaires. The data analysis technique used was a two-way anava test with unequal cells and a Scheffe follow-up test. Before the two-way anava test was carried out, a prerequisite test was first carried out, namely the normality test using the Liliefors test and the homogeneity test using the Bartlett test. The results of the hypothesis test in this study found that (1) the mathematical creative thinking ability of students who obtained the think pair share learning model was better than students who obtained the student team achievement division learning model; (2) there is no difference between students' mathematical creative thinking ability and climber, camper,Â and quitter type adversity quotient; and (3) there is no interaction between the learning model and adversity quotient on students' mathematical creative thinking ability. Â Therefore, the Think Pair Share learning model can be an alternative learning to improve students' creative thinking skills.